Fiquei Homem: Maternidade, Conhecimento e Contracepção entre mulheres pobres de Fortaleza (1960-1980) - Menezes, Valderiza Almeida (2012)
The present research wants to think historically about the experience of poor woman in Fortaleza – Ceará with the contraception in the 1960s and 1970s. The birth control has become a theme very discussed by many subjects from the rise of contraceptive methods like birth control pills, IUD – intrauterine device -, and tubal ligations, as the possibility of a "demographic explosion" in poor countries of Latin America. In this context, State, Civil Society and the Catholic Church undertook a dispute for speech in which the female body was at the center of the question. Thus, this study favored memories of some poor women living in the suburbs of the city of Fortaleza, with the intention of realizing how they remember the use of contraception, whether or not medicalized. The intention is to understand how the models of masculinity and femininity constructed interfered in the everyday of the subjects and how the demand and world view affected the choices made. This discussion is based, mainly, in oral source, medical magazines, family planning civil entity’s publications and newspapers of that time, documents who aloud visualize acquiescence, refusals and adaptation to the proposed ideal.